COVID-19, SDGs and public health systems: Linkages in Brazil - Flavio Martins; Anna Lima; Loan Diep; Luciana Cezarino; Lara Liboni; Rita Tostes; Priti Parikh (Elsevier, 2023)
Background: The global 2030 Agenda covers a range of interconnected issues which need interdisciplinary and holistic approaches to improve human well-being and protect the natural environment. The COVID-19 pandemic has brought to light critical inequities in society and policy gaps in health services. As highlighted through analyses of the interlinkages among the Sustainable Development Goals (SDGs), connections between human health and well-being and the environment, can help support new policy needs in addressing systemic health crises, including widespread pandemics. Method: We identify links between the COVID-19 crisis and multiple SDGs in the context of Brazil based on a review of the current literature in the health sector.Findings: We identify synergistic connections between 88 out of 169 SDG targets and COVID-19, notably around themes such as City Environment, Contextual Policies and the value created by improved Information and Technology. Using the context of the Brazilian National Health Service (SUS) highlights recurrent interconnections from the focal point of target 3.8. This includes topics such as challenges for universal healthcare coverage, budget allocation, and universalisation. Conclusions: The framework developed for supporting policy-making decisions and the design of toolkits for dealing with future health-related emergency scenarios offers a practical solution in the health sector. It is worth noting that progress and action on public health systems and policies must go hand in hand with addressing existing socio-economic vulnerabilities in society. This is vital for tackling future pandemics and simultaneously addressing the SDGs.